(3JZQjO GdUGOMs - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehi GdCRQGQi , GdeYQha HGHf MLI GdMehis; (3GHf GdgHGQjI , eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj,J (B509 (3g` s ((3jG Sjf Hf NjQ Gddg GdNWjH GdYeQi s)
(3ChdgG (B:s
(3hai SfI KdGK YTQI hKeGfeGFI Cda CQLhRI ef CeKGd GdUGOM hGdHGZe , hfXe dgG OjHGLI hNGJeI hSeGgG JZQjO GdUGOM aGf ddBOGH aVdG jPcQ adG JNGWH cd ef dG jTYQ s
(3BNQgG (B:s
(3bdfG LejYG EP SeYfG QLRg ce CJi eMeO HeYLRg Ke GdUdGI hGdSdGe OGFeG Ydi GdPi GdQSd LGA NGJeG s
(3GfXQgG Vef OjhGf GHf MLI Lfi GdLfJjf ef hQbI (B74(3H(B-77(3Hs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3fXes
Keywords: (3GdCOHs